The Effect of Fat Consumption Intake, Obesity and Cholesterol Level On Fertility Of Women - Mudlikah, Siti; Suprapti, Suprapti; Shoihah, Khilyatus (Universitas Islam Lamongan, 2021)
Excess fat intake can lead to accumulation of body fat, obesity, high cholesterol levels cause disruption of female menstrual cycle hormone production. The purpose of study was to determine the effect of excess fat intake, obesity, high cholesterol levels on menstrual cycle and to determine the difference before and after the intervention of a low diet in saturated fat nutrition.The type of research is Analytical Observational study, design Cross Sectional, Logistic Regression Test and T-test of paired sample. Implementation January-June 2021. The population is 480 women of childbearing age (WCA). The instuments are questionnaire and observation. Random sampling technique 218 WCA. The form of nutritional diet intervention is low in saturated fat at least 4-5 days a week for 3 months.Results: Significant fat intake 0.000<0.05. , Obesity 0.001<0.05. Cholesterol level value of 0.001 <0.00 has an effect onÂ menstrual cycle and there is a difference before and after the intervention of diet nutrition low in saturated fat obesity 0.000 <0.05, cholesterol sig 0.000 <0.05, menstrual cycle 0.000 <0.05.Conclusion: Excess fat intake, obesity, high cholesterol levels affect menstrual cycle and there are differences before and after the intervention of a diet low in saturated fat nutrition.